Basis for implementing an integrated pest management program (IPM) in persimmon - García-Martínez, Omar; Urbaneja, Alberto; Beitia, Francisco J.; Pérez-Hedo, Mertixell (ASHS, 2019)
Persimmon has been traditionally considered a minor crop in Spain. However, during the last 20 years, persimmon production has exponentially increased mainly due to the commercialization of the fruit without astringency by a process of modified atmospheres. Due to this, a crop which had few important pests in the past, has become a crop in which some harmful organisms, such as mealybugs (Hemiptera: Pseudococcidae) or honeydew moths (Lepidoptera: Pyralidae), are becoming major pests. With the aim to develop an integrated pest management program (IPM) in persimmon, 5 pesticide-free persimmon orchards located in two production areas in the Valencian Community were chosen to study the presence and dynamics of the arthropods present in this crop (both phytophagous and natural enemies). Stems, leaves, flowers and fruit samples were taken every two weeks during three years (2014-2016). In parallel, persimmon pest species were hierarchized according to their economic impact. The information was used to develop an IPM program for persimmon and made available to the agricultural sector through the IVIA webpage (http://gipcaqui.ivia.es). In this IPM program, pests and natural enemies are identified and described. Sampling methods, economic injury levels and control methods for the main pests are also being developed. Biological control is prioritized as the preferred management method in this IPM program. In this respect, further research is needed to clarify the role of predatory mites (Acari: Phytoseiidae), which are very abundant in this crop.